CONGENITAL LQTS - AN ELECTROCARDIOGRAPHIC AND GENOTYPE CORRELATION - Akhtar, Naveed; Ahmed, Waqas; Mehboob, Mehnaz (Journal of Ayub Medical College Abbottabad, 2005)
The congenital Long QT Syndrome (LQTS) is characterized by abnormally prolonged ventricular repolarization due to inherited defect in cardiac sodium and potassium channels, which predisposes the patients to syncope, ventricular arrhythmias, and sudden cardiac death. Early diagnosis and preventive treatment are instrumental to prevent sudden cardiac death in patients with the congenital LQTS. The diagnostic criteria for congenital LQTS are based on certain electrocardiographic findings and clinical history. Recently genotype specific electrocardiographic pattern in the congenital LQTS has also been described. Recent studies suggest feasibility of genotype specific treatment of LQTS and, in near future, mutation specific treatment will probably become a novel approach to this potentially fatal syndrome. We describe two cases that fulfilled the electrocardiographic and historical diagnostic criteria with morphology on electrocardiogram (ECG) suggestive of LQT1 genotype. Keywords: Congenital LQTS, ECG, genotype, pregnancy